PENGARUH MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - I Nengah Arip Riski Setiawan; Anak Agung Dwi Widyani; Ni Putu Ayu Sintya Saraswati (VALUES, 2022)
The accommodation service business competition is increasingly complex, so a company is required to always pay attention to employee factors, nowadays competition between companies is increasingly competitive, every company is trying to be the most superior among its competitors. Four Seasons has exceptional quality and service. All of that cannot be separated from the quality of Human Resources owned because in services that interact directly with guests, they must have high standards because guests can judge the quality of the hotel from the quality of services provided by employees. This study aims to determine the effect of work motivation on organizational commitment directly or indirectly through employee job satisfaction as a mediating variable at the Four Sessions Hotel And Resort By Sheraton Jimbaran Bali. Sampling was carried out using a saturated sampling technique with a total of 42 employees at the Four Sessions Hotel And Resort By Sheraton Jimbaran Bali. Data processing using Structural Equation Modeling (SEM) analysis techniques with the help of the SmartPLS 3.0 For Windows program. The results of the analysis conclude that work motivation has a positive and significant effect on organizational commitment. Work motivation has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on organizational commitment. And employee job satisfaction is able to mediate the influence of motivation on organizational commitment. The limitations of the research object used only focus on work motivation and employee job satisfaction so that it cannot analyze or reach deeper into the factors that can affect organizational commitment.